Neurocognitive deficits in an adult road traffic accident victim - Anowar, Afsana Benta; Basharat, Anika (Bangladesh Journal of Psychiatry, 2019)
Road traffic accident (RTA) is very common phenomenon in our country and brain injury due to RTA is most common consequence. As there is brain injury, there might be psychiatric manifestation too. A case of neurocognitive disorder due to RTA had been illustrated here. Diagnosis was made by his complaints of forgetting things, self-talking, poor self-care and slowness. Clinician as well as psychiatrists should be aware of the scenario during clinical practice. Bang J Psychiatry 2019; 33(1): 18-19